Equivalent configurations for notch and fretting fatigue - J. A. Araújo; F. C. Castro; S. Pommier; J. Bellecave; J. Mériaux (Fracture and Structural Integrity)
Under the typical partial slip conditions under which fretting fatigue takes place, the amount of superficial damage is small. Therefore, the substantial reduction in fatigue life caused by fretting, when compared to plain fatigue, may well be more associated with the stress concentration and the stress gradient phenomena generated by the contact problem than to the superficial loss of material. In this setting, notch stress-based methodologies could, in principle, be applied to fretting in the medium/high cycle fatigue regime. The aim of this work was to investigate whether it is possible to design fretting and notch fatigue configurations, which are nominally identical in terms of damage measured by a multiaxial fatigue model. The methodology adopted to carry out this search considered a cylindrical on flat contact and a V-notch. Load and geometry dimensions of both configurations were adjusted in order to try to obtain the “same” decay of the Multiaxial Fatigue Index from the hot spot up to a critical distance. Positive results of such simulations can lead us to design an experimental program that can bring more firm conclusions on the use of pure stress-based approaches, which do not include the wear damage, in the modeling of fretting fatigue.